Efektivitas Mesin Simpac Small Stamping 300 T dengan Metode Overall Equipment Effectiveness di PT. XYZ - Apriyanti, Riska; Wahyudin, Wahyudin (Industrika : Jurnal Ilmiah Teknik Industri, 2024)
The machine is the main component in carrying out the production process. Maintenance of production process facilities is an activity to support smooth production. The production process facility in the form of a machine is maintained in the same condition as when it was new or reasonable conditions to carry out operations, when the machine is damaged the production process will be affected and the most fatal process production process stopped Problems at PT. XYZ is a machine that often experiences downtime, after direct observation of problems at PT. XYZ must use the Overall Equipment Effectiveness method to determine the overall effectiveness of equipment with this method the problems of downtime, loss time, cycle time, defects, operation time, and loading time will be known how long the ineffectiveness is, Based on the January 2023 values of 90%, February 90%, and March 84%, and performance calculations in January 99%, February 64%, and March 100%, but in these three months it has not met the international standard in OEE of 85%. Keywords: Down Time, Efektivitas, Loss Time, Overall Equipment Effectiveness